RELATIONSHIP BETWEEN IMPLEMENTATION ACCOUNTING INFORMATION SYSTEM AND CORPORATE GOVERNANCE - Rapina Rapina; Cindy Clarissa Gabriela Febrian (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
The purpose of this study was to determine the relationship between the implementation of accounting information systems on corporate governance. The method used in this study uses quantitative methods using primary data obtained from the distribution of questionnaires or questionnaires. The data to be obtained will be processed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method. Statistical analysis technique using SEM because of the causal relationship between variables. The results of this study indicate that the implementation of the accounting information system has an effect on corporate governance.